Anomaly Field Extraction Based on Layered-Earth Model and Equivalent Eddy Current Inversion: A Case Study of Borehole zk506 in Baishiquan, Xinjiang - Yi Yang; Jie Zhang; Qingquan Zhi; Yang Ou; Xingchun Wang; Lei Wang; Junjie Wu; Xiaohong Deng (Sensors)
Based on the concept of an equivalent eddy current, anomaly field inversion provides an efficient and rapid inversion method for borehole transient electromagnetic (BHTEM) measurements. It enables the utilization of the equivalent eddy current to rapidly process and interpret BHTEM data. This method allows for the accurate determination of the central position and spatial distribution of anomalies. However, the equivalent eddy current method is solely applicable to the inversion of the anomaly field. Given that the measured data frequently contain strong background field information, it is challenging to directly apply the equivalent eddy current approach to the inversion and interpretation of the measured data. To address the aforementioned issues, in this study, we innovatively put forward a method. Specifically, we utilize the response of the layered earth to simulate the background field and subtract the background field from the measured data through the “difference method” to extract the anomaly field. Subsequently, by integrating the equivalent eddy current method, the inversion of the anomaly field was accomplished. Eventually, a rapid quantitative inversion and interpretation of BHTEM data were achieved. We applied this approach to extract the pure anomaly from the measured data of the zk506 borehole in the Baishiquan mining area, Xinjiang, and then conducted equivalent eddy current inversion. The spatial position and distribution characteristics of the concealed ore bodies near the zk506 borehole were successfully pinpointed. Validation by the zk507 and zk508 boreholes confirmed that the main anomaly of the nickel ore body is positioned in the southeast of the boreholes, dipping northwestward. This outcome validates the accuracy of the BHTEM inversion interpretation and rectifies the geological understanding obtained from the zk506 single borehole. It demonstrates the effectiveness and significance of the pure anomaly extraction based on the layered-earth model and equivalent eddy current inversion in the exploration of high-conductivity sulfide ores.